Evaluation of thermal management strategy based on zoning of stress states of a gas turbine disk. (July 2017) - Li, Guo; Bao, Mengyao; Sun, Hexing; Ding, Shuiting
Abstract: Considering that either passive thermal management from thermal protection or active thermal management from thermal loading reorganization is determined by thermal management strategy, this paper proposes an evaluation method based on the zoning of the stress states of a disk for different thermal management strategies to assess the advantages and disadvantages of different thermal loading combinations or distributions at the initial design stage. The theoretical model for thermal management strategies is first established by abstracting the combination of thermal loading parameters ( Q e, Q in and h ¯ ). Subsequently, the zoning principles are defined based on the stress state characteristics. The sensitivity factors S σ , in and S σ , e are introduced to quantify the variation degrees of the thermal loading parameters Q in and Q e for stress state. A rotating turbine disk with a nearly real geometry is used as evaluation object to investigate the effects of different thermal management strategies from three aspects: the position of maximum stress, the iso-surface of the maximum stress level and the variation profile of the disk. Results show that the stress states for each thermal management strategy can be divided into four zones based on the position of the maximum von-Mises stress and the direction of the circumferential stress. A three-dimensional space region partition is generated for each stress state, which shows that the appropriate thermal loading combinations in the design are limited and have an application scope. Generally, the thermal loading combinations in the Domain 1(I) zone represent the most appropriate objects in the design process, whereas the other zones should be avoided because of the enormous negative temperature gradient they produce in the disk. Moreover, the values of sensitivity factors S σ , in and S σ , e in the considered disk profiles are similar, and the effects of the variations in the thermal loading parameters Q in and Q e on the maximum stress are not influenced by the disk profile.